Enhancing Performance In Libyan Manufacturing: A TQM Approach With Zueitina Oil Company (ZOC) As A Case Study (Comprehensive Journal of Science, 2025)
This study explores the reality of implementing Total Quality Management (TQM) as a strategic approach to enhance the overall performance of Libyan manufacturing companies, with a specific focus on the case study of the Zueitina Oil Company (ZOC). Libyan organizations face significant challenges in quality management due to historical practices and a lack of awareness of modern quality frameworks.The aim of this study was to highlight the interconnection of TQM elements and their impact on business performance by understanding how TQM can be a driving factor for operational excellence in the Libyan manufacturing sector. It provides a pathway for organizations to improve quality, increase competitiveness, and achieve sustainable growth. The study identified key success factors such as leadership commitment, employee involvement, and the use of quality tools, including Statistical Process Control (SPC) and Quality Function Deployment (QFD). The findings revealed that the Zueitina Oil Company (ZOC) has made progress in ensuring quality, but still lacks a comprehensive understanding of Total Quality Management (TQM).The study concluded with several recommendations, including the need to promote a quality-centered culture, establish quality assurance departments, continue training programs, and enhance collaborative relationships with suppliers